Reduction of error in determining the cost of construction resources in estimated documentation - Sichnyi, S.B. (Ways to Improve Construction Efficiency, 2020)
In Ukraine, the construction costs in the investor's estimates is calculated by the resource method - using resource element estimation norms. Therefore, the accuracy in determining the components of these norms can cause the error in calculating the construction costs of the object. In this article, the example of construction materials shows the influence of the resource name in the resource element estimation norm on the accuracy of determining the market price of this resource in the estimating documentation, and thus on the accuracy of the construction costs calculation at the stage of the investor‘s costs planning. The main attention is paid to search for the ways to reduce the quantity of the samples, as the main factor influencing the critical indicators - the time and cost of work to determine the market price of the construction materials. The unification of the construction resources names in the resource element estimation norms and a problem of comparison of these names with the real building materials is highlighted in the article too. The examples show which elements in the name of construction materials in the element resource norm contribute to the reduction of the samples quantity and affect the price variation for the samples and the general set of market prices of the relevant materials. This article offers the term "name of the resource for estimation" which generalizes and characterizes the names of materials in DSTU (national standard of Ukraine) and SOU (standards of organization of Ukraine) resource element estimation norms. The rules of formation, use and specification of the "name of the resource for estimation" during the development of resource element norms and at all stages of design and construction of the object are offered too. The author proposes the amendments to the current procedure for the development and revision of resource element estimation norms, which will help to reduce the errors in determining the market price of construction resources during the creation of estimation documentation.